A Prospective Cohort Study of Perceived Noise Exposure at Work and Cerebrovascular Diseases among Male Workers in Japan - Fujino, Yoshihisa; Iso, Hiroyasu; Tamakoshi, Akiko (Journal of Occupational Health, 2007)
This study prospectively examined the association between perceived noise exposure at work and cerebrovascular diseases among Japanese male workers. A baseline survey was conducted between 1988 and 1990, which involved 110,792 inhabitants (age range：40-79 yr) from 45 areas throughout Japan. Subsequent causes of death were identified from death certificates. The analysis was restricted to 14,568 men free of a cerebrovascular diseases (age range：40-59 yr) who were in work at the time of the baseline survey. All subjects completed a self-administered questionnaire at the baseline. This included a question regarding perceived noise exposure at work. The Cox proportional-hazards model was used to estimate the risks of perceived noise exposure for death due to cerebrovascular diseases. The model included age, smoking, alcohol consumption, educational level, perceived mental stress, past medical history, body mass index, hours of walking, hours of exercise, shift work, and job type. During the 190,777 person-years of follow-up, a total of 1,064 deaths were recorded, 98 from cerebrovascular diseases, 27 deaths from subarachnoid haemorrhage, 35 deaths from intracerebral haemorrhage, and 25 deaths from cerebral infarction. Noise exposure did not increase the risk of cerebrovascular diseases, subarachnoid haemorrhage, or cerebral infarction. However, perceived noise exposure increased the risk of intracerebral haemorrhage diseases (hazard ratio (HR)=2.38, 95%Cl：1.20, 4.71, p=0.013). Furthermore, individuals with hypertension were highly susceptible to the effect of perceived noise exposure on the risk of intracerebral hemorrhage, but this association was not observed among the subjects without hypertension. Although the underlying mechanisms are not clear, hypertensive individuals with perceived noise exposure at work should be regarded as a high-risk group for intracerebral hemorrhage.